COMPUTER SCIENCE JOURNALS IN SINTA: A RHETORICAL MOVE ANALYSIS OF RESEARCH ARTICLE ABSTRACTS - Annisa Jullia Chandra, - (2023)
Abstract structures exist as the guides for constructing a good research article (RA) abstract. The importance of structures is confirmed through rhetorical move analysis researches that have been conducted in various disciplines, but abstract research for Computer Science field is infrequent. This study aims to identify rhetorical moves, linguistic features, and the indexation effect in RA abstracts of Sinta-indexed Computer Science journals. Hyland's (2000) five-moves analysis framework was used to examine 120 abstracts from six journals that represented Sinta 1 to 6. Purposive sampling method was implemented by filtering the samples based on Sinta levels and publishing year. The move-step occurrences, saliences, tenses, and voices were analyzed in each sentence of the abstracts. The findings showed that Move 1 - Introduction and Move 3 - Method were the most frequent moves in all Sinta levels. Move 5 - Conclusion was the least frequent in all Sinta levels. Move 1 - Step 1 - Arguing for topic significance, Move 3 - Step 7 - Describing procedure and context, and Move 5 - Step 8 - Evaluating significance of the research were considered as the most dominant. This study also found that present tense and active voice had the highest percentage across all Sinta levels. To conclude, Sinta level has no relation with move-step realizations and pattern. Sinta 6 was discovered solely as an outlier in several observations.